The Effect of Rotation on the Heat Transfer of a Couple Stress Fluid in A Nonuniform Inclined Asymmetrical Channel with Inclined MHD - Hanaa Abdulhussein; Ahmed M. Abdulhadi (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2023)
The purpose of this research is to investigate the effects of rotation on heat transfer using inclination magnetohydrodynamics for a couple-stress fluid in a non-uniform canal. When the Reynolds number is low and the wavelength is long, math formulas are used to describe the stream function, as well as the gradient of pressure, temperature, pressure rise and axial velocity per wavelength, which have been calculated analytically. The many parameters in the current model are assigned a definite set of values. It has been noticed that both the pressure rise and the pressure gradient decrease with the rise of the rotation and couple stress, while they increase with an increase in viscosity and Hartmann number. The explanation of parameters is shown graphically by a series of figures using "MATHEMATICA".